Social Support as A Moderator of the Relationship between Work Family Conflict and Family Satisfaction - Zalam, Zaleha; Ibrahim, R Zirwatul Aida R (PhD); Bakar, Azlina Abu (PhD); Dagang, Mazidah Mohd (PhD) (International Journal of Engineering and Technology, 2018)
The issue of psychological distress is a particular concern for many people, especially workers. However, this issue has not received the attention it deserves. The aim of this study is to investigate the relationship between psychosocial work environment (job control and job demand) and its role in predicting psychological distress (depression, anxiety and stress). A questionnaire survey approach was used as a method of quantitative data collection involving 148 teachers from Kelantan, East Coast of Malaysia. The results revealed a significant correlation between the psychosocial work environment and psychological distress. Multiple regression results also indicated that job control and job demands explained 13%, F (2,145) = 5.37, p <0.01 and 14%, F (2,145) = 3.52, p <0.05 of the variance in teachers’ anxiety and stress, respectively. The results are expected to contribute to the workers and organisations to identify risk potentials and protective factors as guidelines in developing a strategic plan to improve the health of workers.